(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In 2014, the RBI introduced two new categories of banks in the Indian financial system, namely payments banks and small banks. The main objective of introducing these banks is to increase financial inclusion, to extend financial products and services to untapped rural areas. India post payments bank is a new kind of payment bank recommended with the express purpose of extending the reach of banking to the vast majority of the unbanked and unbanked segments of the population. This study presents the framework for How this India Post Payments Bank will be a remarkable step towards providing financial services to customers, especially migrant workers and those from lower income households, and also bring them into the second wave of financial inclusion after the first wave of Pradhan Mantri Jan Dhan Yojana.